Illuminating natural history the art and science of Mark Catesby - McBurney, Henrietta 1956- (Paul Mellon Centre for Studies in British Art, 2021)
This book explores the life and work of the 18th-century English artist, explorer, naturalist, and author Mark Catesby (1683-1749). During Catesby's lifetime, science was poised to shift from a world of amateur virtuosi to one of professional experts. He worked against a backdrop of global travel that incorporated collecting and direct observation of nature. Catesby spent two prolonged periods in the New World--in Virginia (1712-19) and South Carolina and the Bahamas (1722-26)--which he documented in Natural History of Carolina, Florida and the Bahama Islands, the first large-format, color-plate book on the natural history of North America. Interweaving elements of art history, history of science, natural history illustration, painting materials, book history, paper studies, garden history, and colonial history, this volume brings together a wealth of unpublished images as well as previously unpublished letters by Catesby, with contemporary accounts of his collecting and encounters in the wild, and details of the materials and techniques of packing and transporting plants and animals across the Atlantic
Literaturverzeichnis Seite 317-334
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Catesby, Mark -- 1683-1749; Malerei; Illustration; Naturgeschichte -- Fach; Nordamerika